Future climate CO2 can harness ROS homeostasis and improve cell wall fortification to alleviate the hazardous effect of Phelipanche infection in pea seedlings - Shabbaj, Ibrahim I (Plant physiology and biochemistry : PPB, 2021)
Copyright © 2021 Elsevier Masson SAS. All rights reserved.